Identifying summer energy poverty and public health risks in a temperate climate - Zhiting Chen; Kimberley Clare O’Sullivan; Rachel Kowalchuk Dohig; Nevil Pierse; Terence Jiang; Mylène Riva; Runa Das (Climate Risk Management)
Understanding the health risks associated with indoor overheating and the impacts of cooling energy poverty during summer is becoming increasingly urgent as anthropogenic climate change intensifies heatwave events in many places. We report on results from a cross-sectional postal survey undertaken in Summer 2021/2022, conducted in five regions of New Zealand that typically experience some of the highest temperatures nationally. The study revealed that energy poverty is significant issue during summer, with 43% of the respondents identifying cost as a cooling restriction. Indoor overheating commonly affected the health and wellbeing of participants, with 63% reporting adverse health outcomes. Households citing cost as a cooling restriction were significantly more likely to report adverse health outcomes. Renters and indigenous Māori households were disproportionately affected by indoor overheating and the associated health and energy inequities. These findings highlight the growing health risks from indoor heat exposure in warming climatesparticularly in temperate countries like New Zealand, where inhabitants and infrastructure are not adequately prepared to handle heat-related risks. Relying solely on energy-intensive active cooling exacerbates energy poverty and injustice, increasing residential energy demand. Policy interventions should focus on promoting passive, energy-efficient, and sustainable cooling strategies to protect vulnerable populations from heat-related health disparities.